An extended induction motor model for investigation of faulted machines and fault tolerant variable speed drives - Jasim, Omar (2010)
High performance variable speed induction motor drives have been commercially available for industrial applications for many years. More recently they have been proposed for applications such as hybrid automotive drives, and some pump applications on more electric aircraft. These applications will require the drive to operate in the presence of faults i.e. they must be “Fault Tolerant” and be capable of “Fault Ride Through”. The aim of this project was therefore to investigate fault ride through control strategies for induction motor drives, particularly with respect to open circuit winding or power converter faults. Three objectives were identified and addressed to meet this aim.